Clinical predictors of childhood streptococcal pharyngitis - Rulifa Syahroel; Amrin Alkamar; A. Aziz Djamal; Rizanda Machmud (Indonesian Pediatric Society, 2008)
Background Antibiotic prescription for the management of all acutepharyngitis seems to be increasing recently. Streptococcal pharyngitisis the one that has strong indication for antibiotic prescription. Itis quiet hard to distinguish the clinical features of streptococcalpharyngitis from non-streptococcal one.Objective To determine specifically clinical features of streptococcalpharyngitis and distinguish them from non-streptococcal one.Methods We conducted a cross-sectional study on children withacute pharyngitis at Pediatric Outpatient Department Dr. M.Djamil Hospital, Padang from November 2006 until March 2007.Data on clinical features and pharyngeal swab culture results wereanalyzed using chi-square test for clinical predictors. All were thenreanalyzed using multivariate logistic regression.Results Ninety-five children aged 3-13 years were enrolled andpharyngeal swab culture was performed. Group A Î² -haemolyticusstreptococcus was found in 13 children (14%). Absence of cough,sore throat, tonsillar exudates and tender anterior cervicaladenopathy were the clinical predictors for streptococcalpharyngitis and the last two shared highest risk (OR 55.05;31.82). Combination of tonsillar exudates, tender anterior cervicaladenopathy and absence of cough contributed 99,3% probability.Conclusions Streptococcal pharyngitis includes a small part of allchildhood with acute pharyngitis. High grade fever, sore throat,absence of cough, tonsiller excudates and tender anterior cervicaladenopathy were considered as clinical predictors for childhoodstreptococcal pharygitis. Combination of some clinical predictorswill strengthen the probability of streptococcal pharyngitis.